(untitled) (The Pakistan Development Review, 2016)
The fact that happiness does not increase as income increases over time [the Easterlin Paradox (1974)] has puzzled a number of scholars for a number of decades. The latest research on this topic [Easterlin, et al. (2010)] concludes that happiness increases with an increment in income in the short term but it adapts to this income increment in the long term. The objective of this research is to test whether happiness adapts to income increase in the short term using two-period panel Pakistan Socio-Economic Survey [PSES (1998-2001)]. The paper makes use of a unique question on happiness asked in PSES to resolve two issues simultaneously: unavailability of happiness question in period 1 and potential inconsistency of responses to general happiness question. The paper applies Random Effect Ordered Probit model to investigate the hedonic adaptation effect using various formulations used in the happiness economics literature. The results show positive and statistically significant impact of income change on happiness with weak evidence of adaptation to income since it is statistically insignificant. The result is consistent with the studies that show no adaptation during a short period. Among several reasons for hedonic adaptation, falling positive emotions and rising aspirations are discussed along with causes of happiness and policy implications. The significance of the present research lies in the fact that it is the first study in Pakistan that tests the hedonic adaptation to income and hence contributes to the evidence on happiness dynamics. JEL Classification: I31, D60, C25 Keywords: Happiness, Adaptation, Income, Panel Ordered Probit Model